Corona Virus – The Dental Outlook (International Journal of Scientific Research and Management (IJSRM), 2020)
AIM: This review provides an overview of the corona virus and to determine the precautionary recommendations to be taken by the Dental Professionals. BACKGROUND: Corona virus (COVID-19) in no time has captured the world’s attention and is declared as a pandemic by WHO. REVIEW RESULTS: Dental care settings inevitably carry the risk of infection due to the specificity of the procedures and effective preventive measures can help the spread of the infection. CONCLUSION: The outbreak of corona virus had already lead to huge number of deaths and its risk continues to remain high. Infection control measures are necessary to help control the situation. KEYWORDS: Corona virus, Pandemic, Dental considerations